2019
DOI: 10.1016/j.aott.2019.04.006
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic resonance imaging of patients with lateral epicondylitis: Relationship between pain and severity of imaging features in elbow joints

Abstract: ObjectiveThe aim of this study was to determine the inter- and intra-observer reliabilities of magnetic resonance imaging (MRI) for the diagnosis of lateral epicondylitis, to examine whether degree of common extensor tendon (CET) injury is related to other elbow abnormalities on MRI, and to investigate the correlation between elbow abnormalities on MRI and patients' symptoms.MethodsFifty-one patients (32 women and 19 men; mean age: 50 years (range, 22–63)) with a diagnosis of lateral epicondylitis were include… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
40
1
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(45 citation statements)
references
References 21 publications
(43 reference statements)
3
40
1
1
Order By: Relevance
“…LE can thus be easily diagnosed; usually, no further workup is required. 6,24 As LE may be self-limiting in some cases, 3,14,28 first-line treatment should be noninterventional. Bracing as well as oral and topical anti-inflammatory agents are recommended.…”
mentioning
confidence: 99%
“…LE can thus be easily diagnosed; usually, no further workup is required. 6,24 As LE may be self-limiting in some cases, 3,14,28 first-line treatment should be noninterventional. Bracing as well as oral and topical anti-inflammatory agents are recommended.…”
mentioning
confidence: 99%
“…Although It is suggested that there is a correlation between the severity of symptoms andchanges in the MRI [29], the values of those nds still have to be ore elucidated.…”
Section: Discussionmentioning
confidence: 99%
“…MRI has been used widely and is appreciated for its high sensitivity, specificity, and accuracy in the diagnosis of LE. 13 Nevertheless, despite the ability of MRI to reveal a synovial plicae structure, no definitive findings have been described for distinguishing a pathologic plicae from a physiologic plicae. 28…”
Section: Methodsmentioning
confidence: 99%